Comparative study for vegetative propagation of Chondracanthus chamissoi “Yuyo” on three types of substrate in a controlled environment and its viability in the Moquegua region - Zapata-Rojas, Jose Carlos; Gonzales Vargas , Alejandro Marcelo; Zevallos-Feria, Sheyla Amanda (Enfoque UTE, 2020)
The research compares the vegetative propagation of Chondracanthus chamissoi, commonly called "Yuyo" in Peru on three different types of substrate, under laboratory controlled conditions. The substrates used for comparison were; TA; clam leaflet, TB; Fruit mesh, CT; cape of propylene and TP; Concholepas concholepas shell. According to the study, there was better survival in TB; determining the formation of (DFS) from 20 to 23 days, according to the results, the vegetative propagation strategy is viable for commercial escalation in the coast of Moquegua, Peru.